Effect of Aromatherapy Using Bergamot and Lavender Oils on Postpartum Blues - Inke Malahayati; Lenny Nainggolan (Journal of Evidence-Based Care, 2020)
Postpartum adaptation failure can cause a mild psychological disorder in the type of postpartum blues. Various aromatherapy has been tested to treat postpartum blues. This study aimed to compare the effectiveness of aromatherapy using bergamot with lavender oils in postpartum blues. This non-randomized quasi-experimental controlled trial study with a pretest and posttest design was performed on 40 women after cesarean section (C-section) using consecutive sampling. The Edinburgh Postnatal Depression Scale (EPDS) questionnaire was used for the diagnosis of postpartum blues. The participants were given seven drops of aromatherapy oils via a handkerchief inhaled with ten deep breaths for 14 days and then placed next to a pillow. The EPDS scores were measured twice (at the baseline and after 7 days). The data were analyzed using SPSS software (version 21) and the Mann-Whitney U and Wilcoxon tests. The mean EPDS scores before the intervention were 11.4±0.9 and 11.1±1.2 in the bergamot and lavender groups, respectively. The mean EPDS scores on the 7th day of the intervention were 8.8±3.1 and 5.3±2.2 in the bergamot and lavender groups, respectively (P=0.003). Aromatherapy is recommended within the 3rd to 5th day following C-section.